Single dose of BNT162b2 mRNA vaccine against severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) induces neutralising antibody and polyfunctional T‐cell responses in patients with chronic myeloid leukaemia. (3rd June 2021) - Harrington, Patrick; Doores, Katie J.; Radia, Deepti; O'Reilly, Amy; Lam, Ho Pui Jeff; Seow, Jeffrey; Graham, Carl; Lechmere, Thomas; McLornan, Donal; Dillon, Richard; Shanmugharaj, Yogita; Espehana, Andreas; et al.
Summary: Patients receiving targeted cancer treatments such as tyrosine kinase inhibitors (TKIs) have been classified in the clinically extremely vulnerable group to develop severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2), including patients with chronic myeloid leukaemia (CML) taking TKIs. In addition, concerns that immunocompromised individuals with solid and haematological malignancies may not mount an adequate immune response to a single dose of SARS‐CoV‐2 BNT162b2 (Pfizer‐BioNTech) vaccine have been raised. In the present study, we evaluated humoral and cellular immune responses after a first injection of BNT162b2 vaccine in 16 patients with CML. Seroconversion and cellular immune response before and after vaccination were assessed. By day 21 after vaccination, anti‐Spike immunoglobulin G was detected in 14/16 (87·5%) of the patients with CML and all developed a neutralising antibody response [serum dilution that inhibits 50% infection (ID50 ) >50], including medium (ID50 of 200–500) or high (ID50 of 501–2000) neutralising antibodies titres in nine of the 16 (56·25%) patients. T‐cell response was seen in 14/15 (93·3%) evaluable patients, with polyfunctional responses seen in 12/15 (80%) patients (polyfunctional CD4 + response nine of 15, polyfunctional CD8 + T‐cell response nine of 15). These data demonstrate the immunogenicity of a single dose of SARS‐CoV‐2 BNT162b2 vaccine in most patients with CML, with both neutralising antibodies and polyfunctional T‐cell responses seen in contrast to patients with solid tumour or lymphoid haematological malignancies.